Ag-doped SrTiO3: Enhanced water splitting for hydrogen production - Azevedo, Sergio A. [UNESP] (2024)
This study investigates the effect of Ag-doping on the (001) surface of SrTiO3 (STO) to enhance hydrogen production via water-splitting employing density functional theory (DFT) simulations. It was found that the heterolytic water dissociation on Ag-doped (001)-STO occurs via a first-order reaction with an energy barrier of 5.74 kJ/mol, representing a reduction of 94% compared to undoped (001)-STO. The Gibbs free energy of H2 formation catalyzed by Ag-doped (001)-STO is approximately −302 kJ/mol, indicating the spontaneity of this process. Additionally, the surface band gap energy decreases by ∼2 eV after water-splitting, suggesting charge transfer from the Ag-doped STO to the water and leading to new electron-hole recombination states. This research underscores the potential of Ag-doping in enhancing the efficiency of hydrogen production through water-splitting, contributing to the development of greener and more efficient energy technologies.